The Roles of Negative Career Thoughts and Sense of Coherence in Predicting Career Decision Status - Austin, R. Kirk; Dahl, A. Dennis; Wagner, Bruce D. (Canadian Journal of Counselling and Psychotherapy, 2009)
The relationship between sense of coherence and negative career thoughts was investigated in a non-college-based population to determine the relationship and predictive value of these factors toward career decision status. Participants completed the Orientation to Life Questionnaire, Career Thoughts Inventory, and Career Decision Profile’s decidedness and decisiveness subscales. Results indicated strong inverse relationships between sense of coherence and negative career thinking. Regression analysis indicated that sense of coherence and negative career thoughts together accounted for 15% of the variance of career decidedness but 38% of the variance of decisiveness. Implications for counselling are discussed.